PELATIHAN MICROSOFT OFFICE DAN MEDIA PEMBELAJARAN BERBASIS DIGITAL BAGI SISWA-SISWI SD NEGERI 1 SRIKATON - Rini Nurlistiani; Handoyo Widi Nugroho; Andrean Danofic (Institut Informatika dan Bisnis Darmajaya, 2024)
The advancement of information and communication technology (ICT) in the industrial era 4.0 which is increasingly developing affects various fields in life, including one of them in the field of education. One of the objects of service carried out is at SD Negeri 1 Srikaton, Lampung. This service is aimed at 6th grade students because many do not understand the importance of information technology as a means of digital-based learning media such as microsoft office and Canva applications. The purpose of this training is to introduce information technology to students for such as office administration and create content marketing on social media media that is interesting and educational. The methodology used in this service is observation, socialization through presentations, demonstrations and direct practice to the participants, the last is mentoring and evaluation. The results of this service are that students are able to create imagination in designing school assignments, both from templates, colors, and font types in the Canva application. As well as the use of basic Office which is quite easy for participants to understand